2017
DOI: 10.3389/fendo.2017.00132
|View full text |Cite
|
Sign up to set email alerts
|

Resting Metabolic Rate Does Not Change in Response to Different Types of Training in Subjects with Type 2 Diabetes

Abstract: Background and objectivesAmbiguous results have been reported regarding the effects of training on resting metabolic rate (RMR), and the importance of training type and intensity is unclear. Moreover, studies in subjects with type 2 diabetes (T2D) are sparse. In this study, we evaluated the effects of interval and continuous training on RMR in subjects with T2D. Furthermore, we explored the determinants for training-induced alterations in RMR.MethodsData from two studies, both including T2D subjects, were enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Results from the trial are reported in line with the CONsolidated Standards of Reporting Trials guidelines : extension to randomised pilot and feasibility trials (CONSORT guidelines, S3 File) [34]. Other data from this study have previously been published [35,36], but no data on the primary outcome, usability or feasibility reported in this report was disclosed, nor were the group allocations. Flow of participants is presented in Fig 1.…”
Section: Methodsmentioning
confidence: 92%
“…Results from the trial are reported in line with the CONsolidated Standards of Reporting Trials guidelines : extension to randomised pilot and feasibility trials (CONSORT guidelines, S3 File) [34]. Other data from this study have previously been published [35,36], but no data on the primary outcome, usability or feasibility reported in this report was disclosed, nor were the group allocations. Flow of participants is presented in Fig 1.…”
Section: Methodsmentioning
confidence: 92%
“…Most of the studies were a parallel study design except for one crossover study design (Kirk et al, 2009). The majority of studies were conducted in overweight/obese populations that were predominantly sedentary (Akbulut & Rakiciogu, 2012;Bonfante et al, 2017;Bonfanti et al, 2014;Byrne & Wilmore, 2001;Frey-Hewitt et al, 1990;Gornall & Villani, 1996;Hunter et al, 2015;Jennings et al, 2009;Karstoft et al, 2017;Kirk et al, 2009;Kraemer et al, 1999;Meckling & Sherfey, 2007;Rehová et al, 2007;Whatley et al, 1994), two in type-2 diabetic populations (Jennings et al, 2009;Karstoft et al, 2017), one in a population with metabolic syndrome (Bonfanti et al, 2014), several in predominantly normal-weight and/or healthy sedentary populations (Arciero et al, 2006;Cullinen & Caldwell, 1998;Gomersall et al, 2016;Goran et al, 1994;Lee et al, 2009;Miller et al, 2018;Scharhag-Rosenberger et al, 2014) and one in active, healthy populations (Arciero et al, 2001). All studies captured were in adult populations, with several predominately focussing on females (Akbulut & Rakiciogu, 2012;Byrne & Wilmore, 2001;Cullinen & Caldwell, 1998;Gornall & Villani, 1996;Hunter et al, 2015;Meckling & Sherfey, 2007;Miller et al, 2018;Rehová et al, 2007;Whatley et al, 1994), males…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Several interventions were exercise only; with either a predominant focus on aerobic exercise (Frey-Hewitt et al, 1990;Karstoft et al, 2017;Lee et al, 2009), resistance exercise (Bonfante et al, 2017;Byrne & Wilmore, 2001;Cullinen & Caldwell, 1998;Kirk et al, 2009;Miller et al, 2018;Scharhag-Rosenberger et al, 2014) or a combination of both exercise modalities (Gomersall et al, 2016;Jennings et al, 2009). Many studies used a combined dietary and exercise intervention; with four studies using predominantly aerobic exercise (Akbulut & Rakiciogu, 2012;Arciero et al, 2006;Bonfanti et al, 2014;Goran et al, 1994), two in resistance exercise (Arciero et al, 2001;Gornall & Villani, 1996) and five using a combination of both exercise modes (Hunter et al, 2015;Kraemer et al, 1999;Meckling & Sherfey, 2007;Rehová et al, 2007;Whatley et al, 1994).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations